Enhancing Electroreduction CO2 to Hydrocarbons via Tandem Electrocatalysis by Incorporation Cu NPs in Boron Imidazolate Frameworks - Shao, Ping; Wan, Yu‐Mei; Yi, Luocai; Chen, Shumei; Zhang, Hai‐Xia; Zhang, Jian (Small (Weinheim an der Bergstrasse, Germany), 2024)
Due to the higher value of deeply‐reduced products, electrocatalytic CO2 reduction reaction (CO2RR) to multi‐electron‐transfer products has received more attention. One attractive strategy is to decouple individual steps within the complicated pathway via multi‐component catalysts design in the concept of tandem catalysts. Here, a composite of Cu@BIF‐144(Zn) (BIF = boron imidazolate framework) is synthesized by using an anion framework BIF‐144(Zn) as host to impregnate Cu2+ ions that are further reduced to Cu nanoparticles (NPs) via in situ electrochemical transformation. Due to the microenvironment modulation by functional BH(im)3− on the pore surfaces, the Cu@BIF‐144(Zn) catalyst exhibits a perfect synergetic effect between the BIF‐144(Zn) host and the Cu NP guest during CO2RR. Electrochemistry results show that Cu@BIF‐144(Zn) catalysts can effectively enhance the selectivity and activity for the CO2 reduction to multi‐electron‐transfer products, with the maximum FECH4 value of 41.8% at −1.6 V and FEC2H4 value of 12.9% at −1.5 V versus RHE. The Cu@BIF‐144(Zn) tandem catalyst with CO‐rich microenvironment generated by the Zn catalytic center in the BIF‐144(Zn) skeleton enhanced deep reduction on the incorporated Cu NPs for the CO2RR to multi‐electron‐transfer products. A tandem catalyst of Cu@BIF‐144(Zn) is successfully synthesized with uniformly ultrasmall Cu NPs located near the Zn sites according to the BH(im)3− bridge, by a solution impregnation and in situ electrochemical transformation. Electrochemistry results show that Cu@BIF‐144(Zn) catalysts highly improve the selectivity and activity for the CO2 reduction to multi‐electron‐transfer products compared to commercial Cu NPs and BIF‐144(Zn) alone.